2013
DOI: 10.1049/iet-bmt.2012.0059
|View full text |Cite
|
Sign up to set email alerts
|

Session variability modelling for face authentication

Abstract: This paper examines session variability modelling for face authentication using Gaussian mixture models. Session variability modelling aims to explicitly model and suppress detrimental within-class (inter-session) variation. We examine two techniques to do this, inter-session variability modelling (ISV) and joint factor analysis (JFA), which were initially developed for speaker authentication. We present a self-contained description of these two techniques and demonstrate that they can be successfully applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…GMMs have formed the basis of state-of-the-art speaker authentication systems for over a decade [11,9] and it was recently shown that incorporating session variability modelling into a GMM system produces state-of-the-art results for face authentication [12]. Also, the combination of GMM-based systems that use session variability modelling produces a state-of-the-art bi-modal (face and speaker) authentication system [8].…”
Section: Face and Speaker Authentication Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…GMMs have formed the basis of state-of-the-art speaker authentication systems for over a decade [11,9] and it was recently shown that incorporating session variability modelling into a GMM system produces state-of-the-art results for face authentication [12]. Also, the combination of GMM-based systems that use session variability modelling produces a state-of-the-art bi-modal (face and speaker) authentication system [8].…”
Section: Face and Speaker Authentication Systemsmentioning
confidence: 99%
“…In this work, we consider two approaches to session variability modelling, inter-session variability (ISV) modelling [22] and total variability (TV) modelling [9]. Both methods were initially proposed for speaker authentication [22,9] before being applied to face authentication [12,10]. In the remainder of this section, we first describe the GMM baseline system, followed by the more advanced ISV and TV techniques.…”
Section: Gmm-based Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The feature extraction parameters for the GMM/UBM and for the LBP-based classifier were fixed, according to reference values taken from other related works [76,90,91], and they are shown in the Table 4-5 …”
Section: (Hereinafter Lbp-based Classifier)mentioning
confidence: 99%